Apostles of good taste? The use and perception of plaster casts in the enlightenment - Marchand, Eckart (2021)
In his 'Treatise on the Capacity for Sensitivity to the Beautiful in Art …' Winckelmann compares the feeling of the beautiful in art with liquid plaster poured over the head of the Apollo. While this reference to plaster as a material is unusual, his view of casts as propagators of good taste was widely shared. By looking at reactions to casts and cast collections by authors such as Goethe, Christian Gottlob Heyne, John Flaxman and others, this article analyses the complex relationship of notions of good taste on the one side and the perception of plaster casts on the other.